The Influence of Work Motivation and Work Discipline on the Performance of Non-Medical & Medical Support Employees at Medika Hospital BSD - Laila Irawati; Umi Nariawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study was to determine the effect of work motivation and work discipline on the performance of Non-Medical and Medical Support employees at Medika Hospital BSD Tangerang Selatan, either partially or simultaneously. This research is a type of quantitative research. The sampling technique used a saturated sample and the sample obtained in this study amounted to 112 respondents who were the entire population, namely all non-medical employees and medical support at Medika Hospital, BSD Tangerang, South Tangerang. Data analysis used validity test, reliability test, classical assumption test, multiple regression analysis and hypothesis testing using SPSS Statistics 25 application. The result of this study is that work discipline has a significant effect on employee performance by testing the hypothesis obtained tcount > ttable or (5.103 > 1.982) . Thus, Ho1 is rejected and Ha1 is accepted, meaning that there is a significant influence between work discipline on employee performance. Work discipline has a significant effect on employee performance by testing the hypothesis obtained tcount > ttable or (11,561 > 1,982). Thus, Ho2 is rejected and Ha2 is accepted, meaning that there is a significant influence between work discipline on employee performance. Work motivation and work discipline have a significant effect on employee performance with the multiple linear regression equation Y = 8.828 + 0.148 X1 + 0.701 X2 + means the independent variable and the variable bound have a strong degree of relationship. The value of the coefficient of determination is 56.2% while the remaining 43.8% is influenced by other factors. Hypothesis testing obtained fcount > ftable or (70.054 > 3.08). Thus Ho3 is rejected and Ha3 is accepted. This means that there is a simultaneous significant influence between work motivation and work discipline on employee performance.